The influence of support system on self-esteem and adjustment on retired teachers in selected public schools in Iloilo - Cocjin, April L.
This study aimed to know if there exists a relationship between social support and self-esteem as well as relationship between social support system and adjustment among forty retired public school teachers in the selected public schools in Iloilo City., Thirty-five(35) females and five (5) males were selected through snowball sampling. They were retired teachers from selected public schools in the province of Iloilo with ages raging from 56-86 years old. The data gathered were analyzed through Pearson-correlation. This statistical tool was used to determine whether there is an influence of social support system on self-esteem and adjustment among retired teachers. It was found out that there is significant relationship between social support system and adjustment. This could be supported by Pearson r computed (r=.05). However, the results revealed that there is no relationship exists between social support and self-esteem (r=10.25). Several factors were derived by the researchers that have caused the low self-esteem of the respondents. These are civil status, job loss, perception and attitudes of the retired teachers.